Simulation analysis of electric vehicle charging station using hybrid sources - Shriwastava, Rakesh; Kadlag, Sunil Somnath; Pawase, Ramesh; Dhikale, Swati B.; Chavan, Salim; Patil, Hemant R. Bhagat; Chaudhari, Jagdish G.; Sonawane, Pratap Ramesh (International Journal of Applied Power Engineering (IJAPE), 2024)
This paper described simulation analysis of electric vehicle (EV) charging station using hybrid sources. This paper highlights electric vehicle charging station with photovoltaic panels, batteries, and diesel generator. This study employs a solar, battery, diesel generator set, and grid electric vehicle charging station to provide continuous charging in is landed, grid-linked, and Diesel generator (DG) set connected modes. By utilizing a solar and battery, the charging of battery in electric vehicle application is the primary objective If the storage battery is poor and there is no solar generation, The mode of charging automatically shifted to grid or diesel generator set. Furthermore, the charging station manages the generator voltage and frequency without the need of a mechanical speed governor in conjunction with the storage battery. The demand is nonlinear at unity power factor (UPF). For continuous charging, power used from the grid or the DG set and it is synchronized to the grid/generator voltage by the point of common coupling voltage. To boost charging station operating efficiency, the charging station also performs all power transfer from car to grid, vehicle to house, and vehicle to vehicle.